Decolonization of eurocentric knowledge, emancipation of indigenous knowledge and territorialization of life: Decolonization of eurocentric knowledge, emancipation of indigenous knowledge and territorialization of life - LEFF, Enrique (Utopía y Praxis Latinoamericana, 2022)
Five years ago, Maristella Svampa summoned four Latin American colleagues to reflect on the “coloniality of knowledge” in Latin America, starting from a premise and two subsequent questions. The premise: “Many authors have insisted that one of the fundamental features of Latin American social theory is its intellectual or epistemic dependence on the concepts and theoretical frameworks developed in central countries. Some have given theoretical status to this dependence through the concept of "coloniality of knowledge." The questions: “What does it mean to think about social sciences from Latin America in the 21st century in the framework of advanced modernity and in the current system of domination? Is there a Latin American perspective to think about current problems from the framework of social theory? " Part of the answers to these questions will try to be addressed in this article.